The Not So Great Recovery—Economic Policy in the Making of the European Crisis of Youth - Antti Veilahti (Turku Centre for Welfare Research, 2022)
The current economic misery in Europe is often framed as an inescapable consequence of the financial crisis. However, a multilevel comparison based on the European Quality of Life Survey shows that there are important differences in how different countries have faced the crisis. Results show that structural economic changes has contributed to the crisis of employment as much as the sovereign-debt crisis has. Results also suggest that social expenditure has been one of the most efficient ways to support young adults’ employment and wellbeing, while the effects of non-social fiscal stimulation are disadvantageous. This study then argues that while the role of cabinet composition is negligible when controlled for welfare and fiscal policy, the focus should be put on the role of public expenditure and particularly its type. Moreover, in advanced welfare states the effects of the so-called fiscal devaluation are controversial. The study concludes that cuts to social expenditure have not only undermined the relative position of youth but also the sustainability of debt and the long-term prospects of economic and social recovery.